Epidermoid Cyst in the Cerebellopontine Angle: Technical Description Video - de Morais, Marcus Vinicius; Mota, Romulo Almino de Alencar Arrais; Marques, Thais Aparecida; Loduca, Rafael Duarte de Souza; Melo, Paulo Mácio de Porto (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives To describe the operative technique for treatment of epidermoid cysts in the cerebellopontine angle (CPA).Design The present video is a case report.Setting Patient is positioned in three-quarters prone. Retrosigmoid approach should be made under neurological monitoring and with neuronavegation to help achieve maximal safe resection. The skin incision is vertical, slightly curved, 5 mm medial to the mastoid notch. Craniectomy is superiorly limited by the transverse sinus and laterally limited by the sigmoid sinus. A C-shaped durotomy is made with its base protecting the sigmoid sinus. The lesion is removed in piecemeal fashion (Fig. 1). The neurological monitoring helps.Results The patient was discharged 2 days later without neurological deficits.Conclusions The surgical treatment associated with neurological monitoring and neuronavegation is a safe procedure to treat epidermoid cysts in the CPA.The link to the video can be found at: https://youtu.be/sEuFyq9c2sw.
Keywords: epidermoid cyst; cerebellopontine angle lesion; cerebellopontine angle microsurgery; epidermoid cyst surgery